Exploring host community perception of Panchor town for tourist destination based on social exchange theory - Saad, Mazni; Abdullah, Nabilah; Rosman, Siti Nur Hidayah (AMER ABRA cE-Bs by e-International Publishing House, Ltd., UK, 2020)
This paper explores the significance of a rural region, the village of Panchor, as a potential nature tourism site located in Johor district of Muar, Malaysia. The study's objectives were (1) evaluating local community funding, and (2) evaluating the participation of local government. Three overlapping topics were explored based on qualitative interpretation of an interview and open-ended answers in the questionnaire: (1) group connection, (2) economic benefits, and (3) environmental attitude. The findings revealed that river-based tourism could improve the socio-economic status and the sustainability of rural areas. It also addressed the consequences and limitations of the study in this report.